Spectral density from instantons in quenched QCD - Sharan, U; Teper, M (1999)
We investigate the contribution of instantons to the eigenvalue spectrum of the Dirac operator in quenched QCD. The instanton configurations that we use have been derived, elsewhere, from cooled SU(3) lattice gauge fields and, for comparison, we also analyze a random "gas" of instantons. Using a set of simplifying approximations, we find a non-zero chiral condensate. However, we also find that the spectral density diverges for small eigenvalues, so that the chiral condensate, at zero quark mass, diverges in quenched QCD. The degree of divergence decreases with the instanton density, so that it is negligible for the smallest number of cooling sweeps but becomes substantial for larger number of cools. We show that the spectral density scales, that finite volume corrections are small and we see evidence for the screening of topological charges. However, we also find that the spectral density and chiral condensate vary rapidly with the number of cooling sweeps - unlike, for example, the topological susceptibility. Whether the problem lies with the cooling or with the identification of the topological charges is an open question. This problem needs to be resolved before one can determine how important the divergence we have found is for quenched QCD. ©1999 The American Physical Society.